AMPAK ERUPSI GUNUNG MERAPI TERHADAP KAWASAN TAMAN NASIONAL GUNUNG MERAPI (TNGM) DI DIY DANJAWATENGAH - Sugeng Widodo; Sriwidodo Sriwidodo; Irham Irham; Jangkung Handoyomulyo (Universitas Sebelas Maret, 2014)
The purpose of this study was to identify the influence of Merapi eruption on the value of the environment at Merapi TNGM region.Research carried out around the area oh Mount Merapi adjacent to protect forest area TNGM, covering 13 villages namely Kepuharjo, Glagaharjo Hargobinangun sub district, Cangkringan and Pakem Sleman District, Balerante, Tegalmulyo and Sideredjo, Kemalang sub district, Klaten District, Mranggen, Paten, Mangunsoko and Krinjing Villages, Dukun sub district,Magelang District and Tlogolele, Jrakah and Samiran Villages, Selo Sub District, Boyolali District. The samples used were 220 farmers using simple random sampling method. Studied the impact of Merapi eruption was the eruption in 2006 and most of the 2010 eruption. Environmental economic analysis by the method of Contingent Valuation Method (CVM) were used. The results showed that the eruption of Merapi significantly effected on based use value and existence value. Direct use value (dry trees to firewood, grasses and water consumption value) before and after eruption was 5.935 billions and billions 5.457 IDR per year whereas existence value (willining to pay andwilliningnes to accept value) was 223.90 millions and millions 230.16 IDRper year. The indirect use value (biodiversity, conservation and carbon storage value) on 1.51 billions IDR per year. Based on the total economic value (TotalEconomic Value) of protected forest TNGM, a decline of 0.93 %, TEV values before and after eruption was 7.67 billions and billions 7.20 IDR per year.